A Case Study of Malaysian Teachers’ Practice of Play-Based Learning in Preschool - San Li Kheioh; Hui Min Low (Kajian Malaysia, 2022)
Malaysian early education authorities have advocated for play-based learning in Malaysian classrooms in recent years. However, there is minimal recorded evidence of the state of play-based learning implementation in preschools. This study seeks to investigate the practice of play-based learning by three Chinese-ethnic teachers in a preschool. The choice of a case study is to enable a detailed examination of the intertwining relationship between knowledge, attitude and practice of play-based learning among the case study teachers. The findings obtained from three sets of self-report rating and observation point to a stronger influence of knowledge than attitude on the teachers’ practice of play-based learning. Improved knowledge about play-based learning is critical for the Malaysian preschool teachers to apply play-based learning in their teaching practice. Without adequate knowledge in play-based learning, there is the risk that teachers will continue to perceive “play” and “learning” as two separate entities, and correspondingly believe that play has an adverse effect on learning.